Optogenetic activation of leptin- and glucose-regulated GABAergic neurons in dorsomedial hypothalamus promotes food intake via inhibitory synaptic transmission to paraventricular nucleus of hypothalamus - Zesemdorj Otgon-Uul; Shigetomo Suyama; Hiroshi Onodera; Toshihiko Yada (Elsevier, 2016)
Objective: The dorsomedial hypothalamus (DMH) has been considered an orexigenic nucleus, since the DMH lesion reduced food intake and body weight and induced resistance to diet-induced obesity. The DMH expresses feeding regulatory neuropeptides and receptors including neuropeptide Y (NPY), cocaine- and amphetamine-regulated transcript (CART), cholecystokinin (CCK), leptin receptor, and melanocortin 3/4 receptors. However, the principal neurons generating the orexigenic function in the DMH remain to be defined. This study aimed to clarify the role of the DMH GABAergic neurons in feeding regulation by using optogenetics and electrophysiological techniques. Methods: We generated the mice expressing ChRFR-C167A, a bistable chimeric channelrhodopsin, selectively in GABAergic neurons of DMH via locally injected adeno-associated virus 2. Food intake after optogenetic activation of DMH GABAergic neurons was measured. Electrophysiological properties of DMH GABAergic neurons were measured using slice patch clamp. Results: Optogenetic activation of DMH GABAergic neurons promoted food intake. Leptin hyperpolarized and lowering glucose depolarized half of DMH GABAergic neurons, suggesting their orexigenic property. Optical activation of axonal terminals of DMH GABAergic neurons at the paraventricular nucleus of hypothalamus (PVN), where anorexigenic neurons are localized, increased inhibitory postsynaptic currents on PVN neurons and promoted food intake. Conclusion: DMH GABAergic neurons are regulated by metabolic signals leptin and glucose and, once activated, promote food intake via inhibitory synaptic transmission to PVN. Keywords: Dorsomedial hypothalamus, GABAergic neuron, Feeding, Leptin, Glucose, Optogenetics